الأسس الدستورية والقانونية للدولة الإسلامية وتطبيقاتها في خلافة أبي بكر الصديق (رضي الله عنه) - Ahmad Nuryadi Asmawi (Jami'ah al-Islamiyah al-'Alamiyah, 1995)
During the life of the Prophet Muhammad (SAAS) the Ummah were guided and directed by the Divine Revelation. The Messenger of Allah always regulated the affairs of the community in accordance with the principles of the Holy Qur'an. The Companions always consulted the Prophet (SAAS) about certain matters dan problems for seeking Divine Guidance. After the demise of the Messenger of Allah, the task of guiding and leading the Ummah to carry out their lives in accordance with the principles of the Holy Qur'an and the Sunnah lied on the shoulders of his Khalifah (Successors). The Khulafa al-Rashidun were leaders of the Ummah who had rendered great services for the future of Islam and Muslim Ummah. The first period of Khilafah was entrusted to Abu Bakr al-Siddiq (RA). Although Al-Siddiq (RA) remained about two years in the Office of Khilafah, but he had contributed greatly to Islam and served for the future of Muslim Ummah. The most significant contribution of Al-Siddiq (RA) was the unity of the Ummah and the preservation of Islam in its original form. The study of the Khilafah of Abu Bakr al-Siddiq (RA), which was represented the first leadership of Muslim Ummah after the period of the Prophethood, is considered very important especially for young Muslims who wants to understand the concept of Islamic Political System. The First Chapter of this work is designated to discuss the preliminary terminology regarding the concept of "State", "Government" and "Constitution" from the Islamic prespective and Western Constitutional Laws. As a matter of fact, the Khilafah of Abu Bakr al-Siddiq (RA) had complied with all necessary requirements for the concept of a "Modern State", including territory, population, a governing authority, rules and regulations. Even the State of Madinah al-Munawwarah, which was founded by the Messenger of Allah, had its own constitution which was considered the "First Constitution" ever written in the Political History of the World. The Second Chapter of the work is dedicated to analyse the basic principles and characteristics of Islamic State and Polity concerning the repudiation of the idea of dichotomy between the Religion (al-Din) and the State, the political authority of the Ummah which included in "Bay'ah" (taking oath of allegian), "Shura" (mutual consultation), and "Ta'ah" (obedience). The supremacy of Laws, Legal Institution and the principles of Justice, Freedom and Rights are among the essential topics discussed and elaborated in this chapter. The Last Chapter of the work is concentrated on the applications and exercises of the whole concepts, principles of Islamic Polity, Government and State during the Khilafah of Abu Bakr al-Siddiq (RA).